2019
DOI: 10.1177/1477153519894716
|View full text |Cite
|
Sign up to set email alerts
|

Photomorphogenesis of wheat sprouts with LED irradiation of different intensities

Abstract: Definition of the growth and development characteristics of plants in varied light conditions is a key factor for the creation of highly efficient light facilities for plant cultivation. Experimental research was conducted using an LED irradiation facility with photosynthetic photon flux densities ranging from 0 to 261 μmol m−2 s−1 and a continuous spectrum with maxima at 445 and 600 nm. Under the maximum photosynthetic photon flux density (261 μmol m− 2 s−1) wheat germs demonstrated diminishing leaf surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The photoperiod used under blue LED demonstrated the highest accumulation of antioxidant compounds, with significant differences compared to the growth under fluorescent or red lighting. Han et al [51] carried out a similar study in wheat sprouts, the results of which showed that 82 µmol m −2 s −1 blue LED was enough to achieve the maximum leaf parameters and enhance bioactive pigment content (carotenoids and chlorophylls). Similar results were also found by Park et al [52], who studied blue LED in contrast with red and white lighting (50 µmol m −2 s −1 ), results of which showed the highest accumulation of phenolics under blue LEDs and the longest development under red LEDs.…”
Section: Preharvest Uv and Visible Spectrum Illumination Strategies T...mentioning
confidence: 99%
“…The photoperiod used under blue LED demonstrated the highest accumulation of antioxidant compounds, with significant differences compared to the growth under fluorescent or red lighting. Han et al [51] carried out a similar study in wheat sprouts, the results of which showed that 82 µmol m −2 s −1 blue LED was enough to achieve the maximum leaf parameters and enhance bioactive pigment content (carotenoids and chlorophylls). Similar results were also found by Park et al [52], who studied blue LED in contrast with red and white lighting (50 µmol m −2 s −1 ), results of which showed the highest accumulation of phenolics under blue LEDs and the longest development under red LEDs.…”
Section: Preharvest Uv and Visible Spectrum Illumination Strategies T...mentioning
confidence: 99%